The Potential for Bio-Mediators and Biomarkers in Pediatric Traumatic Brain Injury and Neurocritical Care - Kochanek, Patrick M.; Berger, Rachel P.; Fink, Ericka L.; Au, Alicia K.; Bayır, Hülya; Bell, Michael J.; Dixon, C. Edward; Clark, Robert S. (Frontiers in Neurology, 2013)
The use of biomarkers of brain injury in pediatric neurocritical care has been explored for at least 15 years. Two general lines of research on biomarkers in pediatric brain injury have been pursued, 1) studies of “bio-mediators” in cerebrospinal fluid (CSF) of children after traumatic brain injury (TBI) to explore the components of the secondary injury cascades in an attempt to identify potential therapeutic targets and 2) studies of the release of structural proteins into the CSF, serum, or urine in order to diagnose, monitor, and/or prognosticate in patients with TBI or other pediatric neurocritical care conditions. Unique age-related differences in brain biology, disease processes, and clinical applications mandate the development and testing of brain injury bio-mediators and biomarkers specifically in pediatric neurocritical care applications. Finally, although much of the early work on biomarkers of brain injury in pediatrics has focused on TBI, new applications are emerging across a wide range of applications specifically for pediatric neurocritical care including abusive head trauma, cardiopulmonary arrest, septic shock, extracorporeal membrane oxygenation, hydrocephalus, and cardiopulmonary bypass. The potential scope of the utility of biomarkers in pediatric neurocritical care is thus also discussed.